1994
DOI: 10.1002/ijc.2910590325
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of human colorectal‐carcinoma cells by interleukin‐4 and expression of functional interleukin‐4 receptors

Abstract: The growth-inhibitory effect of interleukin-4 (IL-4) was investigated in a panel of 7 human colorectal-carcinoma cell lines. In 5 cell lines (HT29, WiDr, LS411N, LS513, LS1034) a dose-dependent reduction of proliferation was documented. At 100 U/ml, IL-4 inhibited thymidine incorporation between 45 and 75% and MTT conversion (26 to 41%). The ability of LS513 and WiDr cells to form colonies after IL-4 treatment was reduced by 85 and 62% respectively. LS513 was the most sensitive cell line, with IL-4 inducing ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…In normal breast tissues, gp200-MR6 is expressed on both luminal epithelium and myoepithelium (moderate in 86% of cases, strong in 7% of cases). In benign hyperplastic tissues, the expression of gp200-MR6 was heterogeneously distributed, with moderate staining (+ +) in some cells and no staining (-) (Tepper et al, 1989) and an antitumour effect in vivo in the nude mouse xenograft model (Lahm et al, 1994). The role, if any, of gp200-MR6 in such tumour suppression is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In normal breast tissues, gp200-MR6 is expressed on both luminal epithelium and myoepithelium (moderate in 86% of cases, strong in 7% of cases). In benign hyperplastic tissues, the expression of gp200-MR6 was heterogeneously distributed, with moderate staining (+ +) in some cells and no staining (-) (Tepper et al, 1989) and an antitumour effect in vivo in the nude mouse xenograft model (Lahm et al, 1994). The role, if any, of gp200-MR6 in such tumour suppression is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, IL-4 often promotes proliferation, metastasis, and expression of anti-apoptotic genes (13)(14)(15)(16). On the other hand, we and others have shown that IL-4 directly inhibits growth of several human cancer cell lines including those derived from breast, gastric, colon, and renal cancers (17)(18)(19)(20)(21)(22). In addition, apoptosis can be induced or suppressed by IL-4: IL-4 induced apoptosis in certain cell types, including breast and liver cancer cells, hepatocytes, endothelial cells, monocytes, and developing mast cells (23)(24)(25)(26), whereas it increased resistance to apoptosis in mouse fibrosarcoma cell lines and STAT6-high human cancer cell lines such as HT-29 and ZR-75-1 (16,27).…”
Section: Interleukin (Il)mentioning
confidence: 98%
“…inhibits cell growth in several human cancer cell lines with or without inducing apoptosis (17)(18)(19)(20)(21)(22)28). To evaluate the effects of IL-4 on the growth of human RCC cells, Caki-1, A498, and 786-O cells were exposed to 1-10 ng/ml of IL-4 for 24 h, and cell proliferation was measured by a […”
Section: Il-4 Inhibits Growth Of Human Rcc Cells-il-4mentioning
confidence: 99%
“…Other workers have reported that IL-4 inhibited the growth of breast (MCF-7) and colorectal (HT29, WiDr, LS411N, LS513 and LS1034) carcinoma cell lines in culture by 45-75% at 100 U/ml, while competitive binding of 125 I-IL-4 demonstrated the presence of 2,000 high-affinity IL-4 binding sites/cell on the HT29 cell line (Toi et al, 1992;Lahm et al, 1994). It has also been shown that human renal cell carcinoma expresses high-affinity IL-4R and that IL-4 inhibits tumour growth in vitro (Obiri et al, 1993).…”
Section: Both Mab Mr6 and Il-4 Induce Glandular Differentiation Of Swmentioning
confidence: 99%
“…For B cells, T cells, capillary endothelium and mast cells, IL-4 acts as a growth factor (Toi et al, 1991;Defrance et al, 1987;Mosmann et al, 1986;Howard et al, 1982). In contrast, IL-4 has been shown to have a growth inhibitory effect on human colon, renal and breast carcinoma cell lines, (Toi et al, 1992;Obiri et al, 1993;Lahm et al, 1994). Using immunohistochemical and biochemical analysis (Al-Tubuly et al, 1996) for a range of breast tissues, we have demonstrated that gp200-MR6 is weakly expressed on carcinoma in situ and lost on invasive tumours of the breast, while it is strongly expressed on the normal counterparts of the same tissue.…”
mentioning
confidence: 99%